The transformation of the system of representation in the province of Cordoba starting from the application of Sáenz Peña Law (Quinto Sol, 2016)
This paper analyzes the influence that different political actors in the province of Cordoba had in changing the electoral system starting from the application of Sáenz Peña Law in the province context. In Córdoba, liberal democracy ideas echoed throughout the social fabric: Radical Civic Union, local press, and a liberal faction of the ruling class that since 1890 juarismo crisis had stayed away from the power. This pressure for changes on the provincial government of Felix Garzón, responding to a clerical faction of conservatism Cordoba, resulted in the conventional meeting to reform the provincial Constitution. In this context, conventional discourses are analyzed, highlighting similarities and differences within the provincial conservatism and paying special attention to proposals concerning the ideas of democratization of the political-institutional system of the province.
Keywords: Sáenz Peña law; liberal democracy; conservatism; electoral system